REPO AS A SOURCE TO MAINTAIN LIQUIDITY FOR CREDIT ORGANISATIONS - Julia Konopleva; Anzhelika Kopylova; Kseniya Kulakova (Вестник Северо-Кавказского федерального университета, 2022)
Today REPO operations is widespread in Russian and international practice as a tool of the financial market. In this article the essence of REPO operations on the open market, analyzes the current state of this type of operation, as well as the dynamics of the debt of commercial banks for REPO operations. Repo is an essential element of liquidity management of commercial banks in the period of economic instability. The authors were Able to find out the mechanism of REPO in the Russian context in a crisis situation has undergone significant changes due to the expansion of the list offinancial assets.